Representing infirmity
1 online resource.
Keywords: "This volume is the first in-depth analysis of how infirm bodies were represented in Italy from c.1400-1650. Through original contributions and methodologies, it addresses the fundamental yet undiscussed relationship between images and representations in medical, religious, and literary texts. By exploring the works of artists such as Caravaggio, Leonardo, and Michelangelo, this study considers the idealised body altered by diseases including leprosy, plague, goiter, and cancer. The interdisciplinary approach makes this study the perfect resource for both students and specialists of the history of art, medicine and religion, and social and intellectual history across Renaissance Europe"--